GENETIC DIVERSITY AND EVALUATION OF RESTORERS IN AEROBIC CONDITION FOR GRAIN ZINC CONTENT IN RICE (Oryza sativa L.) - K. K. Raghuraman; N. Senthilkumar; P. Senguttuvel; K.R. Saravanan; M.Arivin; P.Thangavel; N. Ramesh (The Bioscan, 2025)
The current research was carried out by Department of Genetics and Plant breeding, Annamalai university, Chidambaram. The experiment trail was conducted at ICAR- Indian Institute of Rice Research, Hyderabad. The aim of this study was to investigate 59 genotypes comprising of 25 back cross inbreed lines (BILs) derived from the cross KMR 3/ N22, thirty-one restorers along with a check under aerobic condition during Kharif, 2023. In this study the back cross inbreed line PSV 6363 has high grain zinc content with 31.10 ppm which higher than the check zincorice.